2014
DOI: 10.1186/1556-276x-9-102
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser-induced formation of silica nanogrids

Abstract: Silica grids with micron to sub-micron mesh sizes and wire diameters of 50 nm are fabricated on fused silica substrates. They are formed by single-pulse structured excimer laser irradiation of a UV-absorbing silicon suboxide (SiO x ) coating through the transparent substrate. A polydimethylsiloxane (PDMS) superstrate (cover layer) coated on top of the SiO x film prior to laser exposure serves as confinement for controlled laser-induced structure formation. At sufficiently high laser fluence, this process leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In order to achieve a smooth, uninterrupted and homogenous bulge along the channel, we implemented shape control through confinement. In our previous work [29], we have shown that the shaping of laser-induced structures is governed by the confinement layer. This involved applying a layer of polydimethylsiloxane (PDMS), which was affixed to the absorbent layer through slight mechanical pressure.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to achieve a smooth, uninterrupted and homogenous bulge along the channel, we implemented shape control through confinement. In our previous work [29], we have shown that the shaping of laser-induced structures is governed by the confinement layer. This involved applying a layer of polydimethylsiloxane (PDMS), which was affixed to the absorbent layer through slight mechanical pressure.…”
Section: Introductionmentioning
confidence: 96%
“…First, laser ablation takes place exclusively when the target substance can efficiently absorb laser radiation. However, in the case of fused silica (SiO 2 ), due to its transparent nature, the absorption of laser radiation is negligible [29]. To address this challenge, we employed a thin coating of silicon suboxide (SiO x , x ≈ 1), known for its strong absorption of UV laser light [30], on the fused silica substrate as the primary material.…”
Section: Introductionmentioning
confidence: 99%
“…Since pulsed ultraviolet laser presents favorable characteristics such as short wavelength, high photon energy, thermal effects which differ from infrared laser, the research into interactions between pulsed ultraviolet laser and materials has aroused universal attentions in recent years [1][2][3][4][5][6][7][8][9][10][11] . High power ultraviolet lasers are expected to be widely applied in precision laser machining and military field.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of spatial confinement on laser-induced structural and phase transformation in [215,216,218], laser-induced forward transfer [219][220][221], thin film patterning/scribing [222,223], and the generation of highquality surface structures [57,239].…”
Section: Discussionmentioning
confidence: 99%